2022
DOI: 10.1155/2022/8690562
|View full text |Cite
|
Sign up to set email alerts
|

Association of Migraine and Irritable Bowel Syndrome in Saudi Arabia: A Nationwide Survey

Abstract: Migraine is a primary headache disorder with a prevalence of 11.6% globally and 27% in Saudi Arabia. Irritable bowel syndrome (IBS) has a prevalence of 9.2% worldwide. The prevalence of IBS has not been established nationally. However, provincial studies for migraine and IBS have been conducted nationwide. There is a significant link between migraine and IBS globally. Migraineurs had a considerably greater prevalence of IBS than nonmigraineurs ( OR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 47 publications
0
11
2
Order By: Relevance
“…Similarly, multiple studies conducted by Chang et al in Asian countries and Hungin et al across eight European countries showed a lower overall prevalence of IBS than our population [ 19 , 20 ]. Moreover, Bin Abdulrahman et al conducted a study on a nationwide scale in the Kingdom of Saudi Arabia, where the results showed a lower IBS prevalence [ 7 ]. As the result implied, the highest prevalence of employees with IBS was in the central region of Saudi Arabia (30.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, multiple studies conducted by Chang et al in Asian countries and Hungin et al across eight European countries showed a lower overall prevalence of IBS than our population [ 19 , 20 ]. Moreover, Bin Abdulrahman et al conducted a study on a nationwide scale in the Kingdom of Saudi Arabia, where the results showed a lower IBS prevalence [ 7 ]. As the result implied, the highest prevalence of employees with IBS was in the central region of Saudi Arabia (30.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea-predominant IBS (IBS-D) was the second-most common (32%), followed by constipation-predominant IBS (IBS-C) (20.6%) and unsubtyped IBS (IBS-U) (2.1%) [ 10 ]. Females outnumbered males in all of the previous national studies [ 7 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that applying the Rome IV criteria has more significant diagnostic acumens than the Rome III principles in the IBS diagnosis, though the clinical relevance is doubtful [8]. Variable prevalence rates of IBS were reported from different regions in Saudi Arabia [9,10]. Therefore, the present study aimed to measure the irritable bowel syndrome IBS frequency and modifiable risk factors amongst medical students at the University of Hail, Saudi Arabia.…”
Section: Introductionmentioning
confidence: 94%
“…According to the findings of a study that was carried out in the Al Jouf district of Saudi Arabia, the prevalence of IBS ranges between 8.9% and 9.2%. The incidence of irritable bowel syndrome (IBS) is considerably higher in persons under the age of 40 compared to those beyond the age of 40 [ 4 ].…”
Section: Introductionmentioning
confidence: 99%